An integrated model for continuance use of cloud computing services towards SMEs organizational performance - Al-Sharafi, Mohammed Abdullah Ali (2020)
The small and medium enterprises’ (SMEs) sector is a major business entity that can significantly benefit from cloud computing services given its flexibility, pay-as-you-go feature and reduced hardware investment. Organisations that adopt cloud computing services as a means of lowering information technology (IT) costs and increasing competitiveness can receive value over time only if they sustained using this technology after implementation. Continuance use of information systems (IS) has become crucial for the sustainability of organisations because they provide efficiency and effectiveness in managing business transactions. Studies on factors that affect the continuance use of this technology have remained lacking, especially on the organisational level, despite numerous research efforts on the initial adoption of cloud computing services. Furthermore, the link between the continuance use of cloud computing services and the SME organisational performance have not been investigated. Therefore, this study aims to bridge the gap in the literature to provide an integrated model for the continuance use of cloud computing services towards SME organisational performance. This model was established by integrating IS continuance model (ISCM) with technology–organisation– environment (TOE) framework in the context of Malaysian SMEs. A total of 15 hypotheses were developed to test the influence of the ISCM and TOE factors on the decision of the continuance use of cloud computing services and their effect on SME performance. An empirical study through a survey methodology was conducted to test the research model. In this respect, 377 valid questionnaires were received from the decision-makers (i.e. owner, CEOs or IT manager) of various Malaysian SME sectors that utilise cloud computing services in their activities. These decision-makers were purposefully selected as sources of data because they were regarded as individuals in the optimum position to answer the questions pertinent to the research problem. Accordingly, partial least squares structural equation modelling (PLS-SEM) using SmartPLS software was utilised to validate the research model and related hypotheses by deploying two statistical tests. These tests include assessing the relationships between constructs and their indicators (the measurement model) and evaluating the relationships between the endogenous latent constructs and exogenous latent constructs (the structural model). Findings show that 11 out of 15 hypotheses are significant and supported (weight>0.1 and t-value>1.65, p-value<0.001). Thus, results show that relative advantage, compatibility, top management support, cost-saving, perceived trust, government support and satisfaction to be significant determinants of SME decision-makers’ behaviour on the continuance use of cloud computing services. Moreover, relative advantage and confirmation influence satisfaction. The results also show a significant relationship between the continuance use of cloud computing services and SME organisational performance. Conversely, other factors, such as complexity, security and privacy, IT readiness and competitive pressure, do not significantly influence the continuance use of cloud computing services. Overall, the research model explains the substantial variance (78%) on the continuance use of cloud computing services, thereby clearly indicating that the developed model is valid and sound. Furthermore, the verification of the developed model was done via a multiple-case study by choosing two Malaysian SMEs. The findings of this study will contribute to existing literature by validating and extending the ISCM with TOE framework in the context of Malaysian SMEs and provide various implications to theory and practice.